An investigation into the interface between three closely spaced axi-symmetric bodies at subsonic speed - Llewelyn-Davies, D. I. T. P. (Cranfield University, 1991)
An experimental investigation has been made into the interference effects present between three closely-spaced bodies over a range of Ø to +6 degrees of either pitch or yaw. Detailed Cp distributions were obtained over the bodies and these were successively intergrated to obtain the loading distribution along the bodies and the overall forces and moments. By analysis of contour maps representing the Cp distribution over the bodies, the loading diagrams, and the overall loads, the extent of the interference regions and their effect on the aerodynamic characteristics of the bodies were determined. A panel method was used to estimate the Cp distributions over the bodies and, as previously, the loading distributions along the bodies and the overall forces. There was close agreement between the estimated and the experimental results over the forebody and the regions where there were appreciable interference effects, but the agreement over the rear of the afterbody was less good. Although the differences between the Cp distributions did not appear large, the differences between the afterbody loadings were appreciable at the higher attitudes with the result that the experimental loads were up to double the estimate. However, an empirical correction method was developed which resulted in the corrected estimates agreeing well with experiment. Estimates were also made of the characteristics of the bodies when the attitude of the body combination was varied between Ø and -6 degrees pitch, and when yaw was varied between Ø and +6 degrees at pitch angles of +6 and -6 degrees.